PERANAN BALAI PEMASYARAKATAN DALAM PEMBINAAN ANAK YANG BERMASALAH DENGAN HUKUM (Studi pada Balai Pemasyarakatan Bandar Lampung) - Purwanto, Sulton M. Arif; Syah, Pairul (SOCIOLOGIE, 2013)
The results of this study indicate that the role of Central Penitentiary Class II A of Bandar Lampung in developing children that conflict with the law are: (1) Implement coaching and guidance to children in trouble with the law. Community mentors provide personal guidance and independence. Guidance personality meant that prisoners have the religious consciousness, awareness and consciousness of nation and state law. Guidance independence is so that inmates can work or create jobs after the prisoners back into society, and not to repeat criminal acts in violation of the law (2) Carry out observations of children in trouble with the law. Supervising Social implement social studies to children in conflict with the law as a report on the development of children in trouble with the law during the process of parole at the Central Penitentiary Class II A of Bandar Lampung.Keywords: Role, central penitentiary, children